1999
DOI: 10.1038/7439
|View full text |Cite
|
Sign up to set email alerts
|

Stable restoration of the sarcoglycan complex in dystrophic muscle perfused with histamine and a recombinant adeno-associated viral vector

Abstract: Limb-girdle muscular dystrophies 2C-F represent a family of autosomal recessive diseases caused by defects in sarcoglycan genes. The cardiomyopathic hamster is a naturally occurring model for limb-girdle muscular dystrophy caused by a primary deficiency in delta-sarcoglycan. We show here that acute sarcolemmal disruption occurs in this animal model during forceful muscle contraction. A recombinant adeno-associated virus vector encoding human delta-sarcoglycan conferred efficient and stable genetic reconstituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 18 publications
4
146
1
Order By: Relevance
“…29,30 A recent report employing intravenous rAAV injection at the time of histamine-induced endothelial permeability demonstrated the transduction of the distal hindlimb musculature. 45 These results strongly imply that improvements in vector delivery and protein expression are achievable. Therefore, safe and efficient transduction seems achievable for AAV-mediated hemophilia B gene therapy.…”
Section: Viral Transduction Was Measured By the Number Of Blue-stainimentioning
confidence: 97%
“…29,30 A recent report employing intravenous rAAV injection at the time of histamine-induced endothelial permeability demonstrated the transduction of the distal hindlimb musculature. 45 These results strongly imply that improvements in vector delivery and protein expression are achievable. Therefore, safe and efficient transduction seems achievable for AAV-mediated hemophilia B gene therapy.…”
Section: Viral Transduction Was Measured By the Number Of Blue-stainimentioning
confidence: 97%
“…The results of immunosupression in later stages by anti-CD4 antibody treatment also support the hypothesis that immune response has been concerned in the AAV-vector mediated gene transfer into mdx skeletal muscle. Several groups have previously demonstrated effective AAV vector-mediated gene transfer into skeletal muscles of mdx mice, 28 ␦-sarcoglycandeficient hamsters (Bio 14.6) 21,22 and ␥-sarcoglycandeficient mice. 23 On the other hand, Cordier et al 24 have shown that an AAV vector driven by CMV promoter elicits strong cellular and humoral immune responses to the transgene product after intramuscular injection into ␥-sarcoglycan-null mice.…”
Section: Figure 7 Effect Of Immunosuppression With Anti-cd4 Antibody mentioning
confidence: 99%
“…[16][17][18]20 Thus, AAV vectors may be applicable to treatment of inherited neuromuscular disorders such as DMD. In fact, the AAV vector has been successfully introduced into ␦-sarcoglycan-deficient hamsters (Bio 14.6) 21,22 and ␥-sarcoglycan-deficient mice, 23 animal models of limb girdle muscular dystrophies (LGMD). A recent report, however, showed lower levels of transgene expression together with substantial immune response to the therapeutic transgene product in ␥-sarcoglycan-null mice.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies documented the administration of various vectors through the vascular route following transient ischemia, chemically induced vasodilatation, 49 or under high physical pressure. 50 The focused ultrasound technology should also be considered. 51 Therefore, naked DNA transfer could be improved by the coupling of one of these approaches to the electrotransfer methodology.…”
Section: Figure 7 Lack Of Persistence Of Transduced Fibers In An Acutmentioning
confidence: 99%